[Houses Along Lava Rock on Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of houses along lava rock on Heimaey. The distressed, white buildings with light red roofs and stone chimneys sit on black dirt and along lava rocks to the left. The rocks cover the black hill on the left edge of the photograph, towering over the buildings. A mountain dusted in white is visible above the cluster of houses to the right, a white cloud hanging over it.